Augment of blessed oils: Canon 847 - Dunn, Brian Joseph (Roman Replies and CLSA Advisory Opinions 2006, 2006)
"After the celebration of the Chrism Mass, the bishop realized that not enough oil was consecrated and blessed so that a sufficient amount could be displayed in larger glass decanters. Should the bishop augment the Blessed Oils with unblessed oils? Under what conditions would a bishop consecrate and bless more oils?"